2017
DOI: 10.2196/jmir.7274
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Cognitive Behavior Therapy for Depression in People With Diabetes Mellitus: A Randomized Controlled Trial

Abstract: BackgroundDepression is twice as common in diabetes mellitus (DM) as the general population and is associated with adverse health outcomes, but access to evidence-based therapies such as cognitive behavioral therapy (CBT) is limited in routine diabetes care. Past research has shown that generic Internet-based cognitive behavioral therapy (iCBT) is an effective treatment for depression in the general population, but it has never been evaluated in people with comorbid depression and DM.ObjectiveThe aim of our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
160
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(176 citation statements)
references
References 50 publications
6
160
2
8
Order By: Relevance
“…According to these criteria, a total of five studies were identified [21,[30][31][32][33]. A summary of the reviewed articles is provided in Table 1.…”
Section: Methods Data Source and Inclusion Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…According to these criteria, a total of five studies were identified [21,[30][31][32][33]. A summary of the reviewed articles is provided in Table 1.…”
Section: Methods Data Source and Inclusion Criteriamentioning
confidence: 99%
“…Three studies had waitlist as control [21,30,31], one added daily emotion reporting [31]. One study used treatment as usual as control [33]. In Nobis and cols study [32], the control group had access to an unguided online brief psychoeducation program for depression.…”
Section: Studies Designmentioning
confidence: 99%
See 3 more Smart Citations